Electrospun Scaffolds Based on a Pcl/Starch Blend Reinforced with Cao Nanoparticles for Bone Tissue Engineering - Orihuela-Diaz, P; Zapata-Ramirez, P; Saavedra-Gonzalez, M; Guzman-Soria, A; Cordoba-Manrique, A (Elsevier B.V., 2024)
Electrospun nanocomposite scaffolds with improved bioactive and biological properties were fabricated from a blend of polycaprolactone (PCL) and starch, and then combined with 5 wt% of calcium oxide (CaO) nanoparticles sourced from eggshells. SEM analyses showed scaffolds with fibrillar morphology and a three-dimensional structure. The hydrophilicity of scaffolds was improved with starch and CaO nanoparticles, which was evidenced by enhanced water absorption (3500 %) for 7 days. In addition, PCL/Starch/CaO scaffolds exhibited major degradation, with a mass loss of approximately 60 % compared to PCL/Starch and PCL/CaO. The PCL/Starch/CaO scaffolds decreased in crystallinity as intermolecular interactions between the nanoparticles retarded the mobility of the polymeric chains, leading to a significant increase in Young s modulus (ca. 60 %) and a decrease in tensile strength and elongation at break, compared to neat PCL. SEM-EDS, FT-IR, and XRD analyses indicated that PCL/Starch/CaO scaffolds presented a higher biomineralization capacity due to the ability to form hydroxyapatite (HA) in their surface after 28 days. The PCL/Starch/CaO scaffolds showed attractive biological performance, allowing cell adhesion and viability of M3T3-E1 preosteoblastic cells. In vivo analysis using a subdermal dorsal model in Wistar rats showed superior biocompatibility and improved resorption process compared to a pure PCL matrix. This biological analysis suggested that the PCL/Starch/CaO electrospun mats are suitable scaffolds for guiding the regeneration of bone tissue. © 2024 Elsevier B.V.